2000
DOI: 10.1016/s0002-9440(10)65072-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations of the APC Gene in Primary Breast Cancers

Abstract: APC gene mutations play an important role in the initiation step of colorectal carcinogenesis in both familial adenomatous polyposis (FAP) patients and non-FAP patients. Although the APC gene is expressed in most tissues, including the lung, liver, kidney, and mammary gland, its somatic mutations have rarely been found in primary tumors affecting these organs. We have developed a sensitive yeast-based assay for screening almost the entire coding region of the APC gene. By this method, we have been able to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 26 publications
5
74
0
Order By: Relevance
“…22,23 Moreover, they can be related to progression of disease, e.g., breast cancer. 24 Only very few sarcomas carry mutations of the APC gene, 11,25 which is consistent with our finding that none of the 15 analysed myxoid/ round-cell LPS showed a truncated APC protein in the PTT assay. Interestingly, APC mutations found in synovial sarcoma are missense mutations.…”
Section: Discussionsupporting
confidence: 89%
“…22,23 Moreover, they can be related to progression of disease, e.g., breast cancer. 24 Only very few sarcomas carry mutations of the APC gene, 11,25 which is consistent with our finding that none of the 15 analysed myxoid/ round-cell LPS showed a truncated APC protein in the PTT assay. Interestingly, APC mutations found in synovial sarcoma are missense mutations.…”
Section: Discussionsupporting
confidence: 89%
“…26,27 We also previously reported that there were no mutations of the APC gene in 29 NSCLCs, including 13 specimens analyzed for ␤-catenin gene mutation in the current study. 28 These findings suggest that APC-mediated nuclear export of ␤-catenin can help form the cadherin-catenin complex. Another possible mechanism is apoptosis by ␤-catenin.…”
Section: Discussionmentioning
confidence: 94%
“…Loss of APC expression and upregulation of b-catenin have been described in human breast cancer and breast cancer cells (Ho et al, 1999;Jonsson et al, 2000;Schlosshauer et al, 2000). Somatic APC mutations are reported in only a minority of breast cancers (Furuuchi et al, 2000), despite high rates of allelic loss at chromosome locus 5q21 (Thompson et al, 1993;Medeiros et al, 1994). Nevertheless, epigenetic inactivation of APC due to DNA methylation is frequently present in both breast cancer cell lines and breast cancer tissue.…”
mentioning
confidence: 99%